TIPOLOGI KLAUSA RELATIF BAHASA JAWA RAGAM KRAMA DIALEK SURAKARTA - Azizah, Nurul (Balai Bahasa Provinsi Daerah Istimewa Yogyakarta, 2023)
This study reveals the typology of relative clauses of the Javanese language variety of Surakarta dialect in terms of the theory of relative clauses of Keenan & Comrie (1977). This type of research is descriptive qualitative with three stages of research, namely data collection, data analysis, and presentation of the results of data analysis. Data collection was carried out using an introspective method based on the researcher's knowledge as a Javanese native speaker. Data analysis uses the distribution method. Presentation of data analysis using informal methods. The theory used is the theory of grammatical relations, namely the relative clause (Keenan & Comrie, 1977). The results of this research show that the Javanese krama (BJK) corresponds to the universality of the relative clauses of Keenan & Comrie (1977) which classifies Javanese as a relative subject language (SU). If in a language there is only one relative constituent, that constituent is the subject. This statement is also in accordance with BJK which can only relativize SU. As for relativization in a non-subject position, it is achieved passively. This study investigated the relativization of beneficial, locative, instrumental, and patient SU. Based on the study, the results show that each SU has implications for the presence/absence of dipun words and affixes –aken or –ake. Relation with actors I, II, III also has its own characteristics, especially in relation to the presence of the word dipun and affixes –aken or –ake.Penelitian ini mengungkap tipologi klausa relatif bahasa Jawa ragam krama dialek Surakarta ditinjau dari teori klausa relatif Keenan & Comrie (1977). Jenis penelitian ini adalah deskriptif kualitatif dengan tiga tahap penelitian, yakni pengumpulan data, analisis data, dan penyajian hasil analisis data. Pengumpulan data dilakukan dengan metode introspektif berdasarkan pengetahuan peneliti sebagai penutur jati bahasa Jawa. Analisis data menggunakan metode distribusional atau disebut juga dengan metode agih. Penyajian hasil analisis data menggunakan metode informal. Teori yang digunakan adalah teori grammatical relations, yakni relative clause (Keenan & Comrie, 1977). Hasil penelitian menunjukkan bahwa bahasa Jawa krama (BJK) sesuai dengan keuniversalan klausa relatif Keenan & Comrie (1977) yang mengelompokkan bahasa Jawa sebagai bahasa perelatif subjek (SU). Jika dalam sebuah bahasa hanya terdapat satu konstituen yang direlatifkan, konstituen tersebut adalah subjek. Pernyataan itu sesuai juga dengan BJK yang hanya dapat merelatifkan SU. Adapun perelatifan pada posisi non-subjek ditempuh dengan pemasifan. Penelitian ini mengamati perelatifan SU benefaktif, lokatif, instrumental, dan pasien. Berdasarkan kajian, diperoleh hasil bahwa masing-masing SU berimplikasi pada hadir/tidaknya kata dipun dan afiks –aken atau –ake. Perelatifan dengan aktor I, II, III juga memiliki karakteristik tersendiri terutama dalam kaitannya dengan kehadiran kata dipun dan afiks –aken atau –ake.